The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3324/haematol.2018.200204
|View full text |Cite
|
Sign up to set email alerts
|

First-line therapy in chronic lymphocytic leukemia: a Swedish nation-wide real-world study on 1053 consecutive patients treated between 2007 and 2013

Abstract: The aim of this study was to investigate long-term outcome following first-line therapy in consecutive chronic lymphocytic leukemia (CLL) patients in a well-defined geographic area: Sweden. All patients diagnosed with CLL (2007–2013) (n=3672) were identified from national registries, screening of patient files identified all (100%) treated first line (n=1053) and for those, an in-depth analysis was performed. End points were overall response rate, progression-free survival (PFS), overall survival (OS), and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 44 publications
11
35
2
Order By: Relevance
“…This is in accordance with data from the German CLL Study Group and other groups showing that treatment with an anti-CD20 antibody is associated with a better overall survival [28][29][30]. Recently a nation-wide real-world study from Sweden reported no survival improvement between 2007-2013 looking at 1053 patients receiving first-line therapy [36]. First-line therapy consisted of chlorambucil in 39% of patients without an anti-CD20-antibody in 95%.…”
Section: Survivalsupporting
confidence: 88%
See 2 more Smart Citations
“…This is in accordance with data from the German CLL Study Group and other groups showing that treatment with an anti-CD20 antibody is associated with a better overall survival [28][29][30]. Recently a nation-wide real-world study from Sweden reported no survival improvement between 2007-2013 looking at 1053 patients receiving first-line therapy [36]. First-line therapy consisted of chlorambucil in 39% of patients without an anti-CD20-antibody in 95%.…”
Section: Survivalsupporting
confidence: 88%
“…Our routine care patient cohort had a median age at diagnosis of 67 , which is comparable to data from Spain [34], and a median age at first treatment of 70 . Median age at start of first-line therapy was 71 (31-96) in a Swedish registry [36] and 68 in an American cohort study [37]. The age of our patient population, therefore, seems to be in a range comparable to other real-world data analyzes.…”
Section: Survivalmentioning
confidence: 59%
See 1 more Smart Citation
“…Our early sceening revealed, in line with Swedish CLL guidelines, that BR was the predominant first‐line therapy used in elderly in the time period studied and that chlorambucil was no longer commonly used in our region (Fig S1), in contrast to an earlier time period, i.e. before bendamustine was generally available 18 . Approval of the Ethics committee was obtained before commencement of the study.…”
Section: Methodsmentioning
confidence: 66%
“…Referrals from outside rarely occur and each patient file can be identified and used for in‐depth analysis. Thus, we have an optimal chance to obtain reliable real‐world data on consecutive patients treated in routine clinical care 18 …”
mentioning
confidence: 99%